Model Program Pemberdayaan Masyarakat Desa Berbasis Komunitas - Hilman, Yusuf Adam; Nimasari, Elok Putri (Universitas Muhammadiyah Ponorogo, 2018)
This study examines the issue of community empowerment, which is considered to be a solution problem of poverty, which is more interesting when the community of